Analysis of the Effect of Internal Communication on Acceptance of Change in the Context of Organizational Management - Dian Mei Suri; Nuri Aslami (Jurnal Fokus Manajemen, 2023)
This study aims to analyze the effect of internal communication on change acceptance in the context of organizational management. Change is inevitable in the business world, and the successful implementation of change is highly dependent on employee acceptance and participation. Effective internal communication has an important role in shaping employees' perceptions and attitudes towards organizational change. This study used a survey method and data were collected through questionnaires distributed to employees at various levels of the organization. Regression analysis was used to examine the relationship between internal communication variables and change acceptance. The results showed that good internal communication has a significant positive influence on change acceptance. Factors such as transparency, message clarity, mutual interaction, and management support in internal communication play an important role in increasing change acceptance by employees. The findings provide important implications for organizational management in designing effective communication strategies to support organizational change.